Communication in the presidential primaries : candidates and the media, 1912-2000 - Kendall, Kathleen E., 1937- (Praeger series in political communication., 2000)
A comparison of communication in the US presidential primaries of the 20th century. It examines the role of the candidates and the media during primary elections and the communication patterns that transcend time regarding political image, horse race coverage and negative campaigning.